(untitled) (Italiano LinguaDue, 2020)
I dati empirici di questo studio sull’italiano scritto di studenti nativi e alloglotti sono costituiti dalle prove d’esame del corso di Didattica dell’italiano L2 previsto nei corsi di laurea triennale e magistrale della Facoltà di Lingue dell’Università di Bologna. Tali prove comprendono due domande a risposta aperta e brevi comunicazioni di apprendenti di italiano L2 da analizzare in un’ottica acquisizionale. Lo studio esamina, in particolare, i tratti macro-linguistici dei testi manoscritti dagli studenti universitari, identificando, sul piano della competenza testuale, contiguità o distanze tra i nativi e gli alloglotti. In base ai risultati, si formuleranno alcune proposte per una didattica della scrittura efficace sia per parlanti nativi che per alloglotti. Written academic discourse by university students in exams: a comparison between Italian L1 and L2 The empirical data for this study is based on written Italian exams by native students and allophones for the course Teaching Italian L2, part of both the three-year and master’s degree courses at the Faculty of Languages, University of Bologna. These tests include two open-ended questions and short texts by Italian L2 learners, analyzed from an acquisition perspective. The study examines, in particular, the macro-linguistic features of the texts written by university students, identifying contiguity or distance between natives and allophone students in terms of textual competence. On the basis of the results, proposals are made for teaching writing to both native speakers and allophones.